AN ANALYSIS OF IMPOLITENESS STRATEGIES USED BY INDONESIAN NETIZENS ON TWITTER WITH #Usuttuntaskanjuruhan: A Case Study of Hate Speech - Tri Bayu Febriyanto, - (Universitas Pendidikan Indonesia, 2023)
The Kanjuruhan tragedy in the last 2022 became a concern for people all over the world. It caused hundreds of people to die. Numerous people commented on this tragedy on Twitter. Many Indonesian netizens commented in an impolite way. This study focuses on the impoliteness strategies used by Indonesian netizens on Twitter concerning the case of the Kanjuruhan disaster. This study aims to reveal the impoliteness strategies used and the possibility of impolite expression leading to hate speech. It examines the impolite expressions to raise people's awareness of their tweets has a chance to lead to hate speech. The descriptive qualitative method is used in this study to describes and interprets impolite expression from Indonesian netizens. This research was conducted by implementing impoliteness strategies types by using Culpeper's (1996) framework. The result showed four impoliteness strategies which are bald on record impoliteness with a percentage of 40.00%, positive impoliteness in 26.67%, negative impoliteness in 20.00%, and mock politeness or sarcasm with a percentage of 13.33%. Bald on record impoliteness is the most common impoliteness to be used in tweets concerning the Kanjuruhan case by using #usuttuntaskanjuruhan. From the analysis, the impolite expression has a huge chance of leading to hate speech.